2000
DOI: 10.1212/wnl.54.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment on free and cued selective reminding predicts dementia

Abstract: Poor performance on free recall from FCSR predicts future dementia. These findings support the existence of a preclinical phase of dementia characterized by memory impairment, which is present for at least 5 years before diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
304
1
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(320 citation statements)
references
References 44 publications
11
304
1
4
Order By: Relevance
“…All three were more sensitive to AD than non-AD dementias due to the focus on memory in both stages of the strategies. Tests like the FCSRT and the MIS, which use controlled learning, powerfully discriminate between normal aging and dementia (Buschke, 1984;Buschke et al, 1995Buschke et al, , 1999Gebner et al, 1997;Grober et al, 1988Grober et al, , 2000Grober & Kawas, 1997;Ferris et al, 2006, Neuropsychological strategies for detecting early dementia 137 Peterson et al, 1994Peterson et al, , 1995Tounsi et al, 1999;Tuokko & Crockett, 1989). FCSRT, the memory test used here, has high sensitivity and specificity for the identification of dementia (Ferris et al, 2006;Gebner et al, 1997;Grober et al, 1988;Peterson et al, 1994;Tuokko & Crockett, 1989), and preclinical dementia (Grober & Kawas, 1997;Grober et al, 2000;Peterson et al, 1995;Robert et al, 2006;Sarazin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All three were more sensitive to AD than non-AD dementias due to the focus on memory in both stages of the strategies. Tests like the FCSRT and the MIS, which use controlled learning, powerfully discriminate between normal aging and dementia (Buschke, 1984;Buschke et al, 1995Buschke et al, , 1999Gebner et al, 1997;Grober et al, 1988Grober et al, , 2000Grober & Kawas, 1997;Ferris et al, 2006, Neuropsychological strategies for detecting early dementia 137 Peterson et al, 1994Peterson et al, , 1995Tounsi et al, 1999;Tuokko & Crockett, 1989). FCSRT, the memory test used here, has high sensitivity and specificity for the identification of dementia (Ferris et al, 2006;Gebner et al, 1997;Grober et al, 1988;Peterson et al, 1994;Tuokko & Crockett, 1989), and preclinical dementia (Grober & Kawas, 1997;Grober et al, 2000;Peterson et al, 1995;Robert et al, 2006;Sarazin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the FCSRT has promise as a demographically neutral memory test because performance in nondemented elderly is unrelated to race or education (Grober et al, 1998;Ivnik et al, 1997). Memory testing is critical to dementia screening because impaired memory is one of its earliest manifestations (e.g., Elias et al, 2000;Grober et al, 2000;Linn et al, 1995;Saxton et al, 2004;Tierney et al, 2005) and because memory is the only cognitive domain that must be impaired to diagnose dementia (American Psychiatric Association, 1994). Postmortem series have demonstrated that memory decline precedes decline in mental status in early pathologically defined AD (Grober et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations